Overall safety profile of boceprevir plus peginterferon alfa‐2b and ribavirin in patients with chronic hepatitis C genotype 1: a combined analysis of 3 phase 2/3 clinical trials. (9th October 2013) - Manns, Michael P.; McCone, Jonathan; Davis, Mitchell N.; Rossaro, Lorenzo; Schiff, Eugene; Shiffman, Mitchel L.; Bacon, Bruce; Bourliere, Marc; Sulkowski, Mark S.; Bruno, Savino; Balart, Luis; Bronowicki, Jean‐Pierre; et al.
Abstract Background & Aims Triple therapy with peginterferon/ribavirin (PR) plus an NS3 protease inhibitor has emerged as the standard‐of‐care for patients with chronic hepatitis C genotype‐1. We provide a detailed safety analysis comparing PR to boceprevir plus PR (BOC/PR) across three phase 2/3 studies. Methods SPRINT‐1 was an open‐label phase 2 study in 595 treatment‐naive patients. In the two phase 3 studies, 1500 patients (1097 treatment‐naive, SPRINT‐2; 403 treatment‐failure, RESPOND‐2) were randomized to receive PR alone, or one of two regimens where BOC was added to PR after a 4‐wk PR lead‐in. In this analysis, the respective BOC/PR and PR arms were combined for all three trials. The benefit of shortened duration of treatment using response‐guided therapy (RGT) was also explored in the SPRINT‐2 trial. Results Only two adverse events, anaemia and dysgeusia, occurred 20% more often with the BOC‐containing regimens compared with PR. Nausea, diarrhoea and neutropenia were the only other common events with an incidence of at least 5% greater when BOC was added to the PR backbone. The proportions of patients reporting serious adverse events (AE), life‐threatening AEs, and study drug discontinuation because of an AE were similar in the PR and BOC/PR arms. In treatment‐naive patients, RGT generally did not result in a lower frequency of common AEs; however, RGT led to decreased exposure to all 3 study drugs and to a decrease in the mean duration of several clinically relevant AEs such as anaemia, neutropenia, fatigue and depression, as well as earlier normalization of haemoglobin and neutrophil counts. Conclusions The safety profile of BOC combination therapy largely reflects the known profile of peginterferon and ribavirin, with incremental haematolgical effects and dysgeusia. Shorter treatment duration with RGT significantly reduced the duration of AEs.